2003
DOI: 10.1002/jbm.a.10595
|View full text |Cite
|
Sign up to set email alerts
|

Ion release in stable hip arthroplasties using metal‐on‐metal articulating surfaces: A comparison between short‐ and medium‐term results

Abstract: The use of metallic heads articulating with metallic cups could solve the problem of polyethylene (PE) wear in total hip replacement (THR) with metal-on-PE bearings. A conspicuous release of metal ions from new models of metal-on-metal bearings has been found in the short-term, but it is yet unclear whether the medium-term corrosion rate is high or, on the contrary, it becomes negligible, because of the continuous surface finishing. Our purpose was to compare the serum ion values (nanograms per milliliter) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 58 publications
3
39
1
2
Order By: Relevance
“…The authors interpreted their findings as suggesting a negative influence on the immune system. Savarino et al [13] reported haematological and immuno- logical alterations in patients with metal-on-metal or metalon-polyethylene arthroplasty, whereas these effects could not be observed in patients with ceramic-on-ceramic prostheses. These findings led on to the hypothesis that metal ions, especially Co and Cr, might have a toxic effect on myelopoesis and the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors interpreted their findings as suggesting a negative influence on the immune system. Savarino et al [13] reported haematological and immuno- logical alterations in patients with metal-on-metal or metalon-polyethylene arthroplasty, whereas these effects could not be observed in patients with ceramic-on-ceramic prostheses. These findings led on to the hypothesis that metal ions, especially Co and Cr, might have a toxic effect on myelopoesis and the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Imanishi et al [9], Back et al [6], Daniel et al [5], Engh et al [10], Antoniou et al [11], Witzleb et al [12] and Savarino et al [7,13] demonstrated that the levels of Co and Cr ions increase within the first three months to two years following metal-on-metal THA. In the study of Imanishi et al [9], there was no significant additional increase of serum metal ion concentration at the one year follow-up, whereas Back et al [6] and Daniel et al [5,14] observed a decreasing trend of serum concentration between one and six years.…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical use of MOM THA is increasing in popularity, concerns remain regarding wear and corrosion of the bearing surfaces and the consequent increase in metal ion serum levels [10,26,31,32,35]. It is certain that metal ions are released because of the combined effect of corrosion of the implant surface and wear particles.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this variability, however, the levels of serum chromium reported for patients with metalon-metal hip arthroplasties have been reasonably consistent, averaging 2.0 µg/L (Jacobs et al 1996, Brodner et al 1997, MacDonald et al 2003, Savarino et al 2003, MacDonald 2004, Dunstan et al 2005, Heisel et al 2005. Despite the recent interest in metal ion release from arthroplasty, few studies dealing with metal ion release from fracture fixation devices have been published.…”
Section: Discussionmentioning
confidence: 99%